Seismic behaviour analysis of a wind turbine tower affected by sea ice based on a simplified model - Shuai Huang; Qingjie Qi; Shufeng Zhai; Wengang Liu; Jianzhong Liu (Scientific Reports, 2021)
Abstract Ice-structure interaction threatens the safety of the offshore structure; however, dynamic seismic action even renders this process more sophisticated. This research constructed a simplified calculation model for the wind turbine tower, ice, and water under seismic loading, which could avoid solving the complex non-linear equations. Then, the seismic behaviour of the structure, i.e. wind turbine tower, in the presence and absence of influences of the sea ice was investigated, and we found the remarkable effect of sea ice upon the wind turbine tower when its mass is within a range; the wind turbine tower is found to have reduced capacity in energy dissipation, and thickness of tower walls or stiffening ribs is supposed to be enlarged for making the structure more ductile. Affected by the sea ice, the shear force and bending moment of the tower showed significant increases, and more attention needs to be paid to the tower bottom and action position of the sea ice. According to the dynamic similarity principle, finally paraffin was used to simulate sea ice, and shaking-table tests were performed for simulating dynamic ice-structure-water interactions. Results of shaking-table tests verified the rationality of our proposed simplified model.